Gastronomy Tourist’s experience: Evidence from Gudeg “Yu Djum” Yogyakarta - Wachyuni, Suci Sandi; Demolingo, Ramang H.; Wiweka, Kadek (Institut Pariwisata Trisakti, 2021)
This research aims to analyze the tourist experience of Yogyakarta gastronomic tourism, especially in Gudeg Yu Djum. This review adopts a quantitative descriptive method and involves 100 respondents as a sample. Meanwhile, data collection was carried out from February to May 2020. The results showed a positive response from respondents in this study related to the experience of eating at Gudeg Yu Djum. Most of the respondents have a special purpose for gastronomic tours, others made gastronomic tours as side trips from primary trips such as nature and cultural tourism. The order of the highest level of impression in developing the gastronomic experience starts from authenticity, sociability, emotions, deliberate and incidental gastro-tourists, travel stages, foodie risk-taking, and Interdependent co-created tourist-host relationship. The theoretical implication in this study is to determine the order of the sub-variables starting from the most decisive in building gastronomic experience. Additionally, the practical implication is that it can provide rich information as an insight for culinary entrepreneurs, particularly to establish a post-pandemic gastronomic tourism business. Since the sample size is limited to one type of restaurant, further research is expected to cater to more restaurants representing gastronomic tourism in Yogyakarta, as well as other cities. Keywords: Gastro-Experience, Gastronomy Tourism, Gudeg, Local Culinary, Tourist Experience